Prevalence and Complications of Mesiodens: a Radiographic Study in a Group of Turkish Pediatric Population - Mahmut Tankuş; Muhammet Bahattin Bingül (Ankara University, 2022)
Objective: This study aims to assess the prevalence of mesiodens in a Turkish pediatric population and to radiographically investigate the characteristics of mesiodentes and the complications caused by them. Materials and Method: This study examined panoramic radiographs of 8002 patients aged 4-16 years. Patients were evaluated for age, gender, dentition status, the number, shape, and position of mesiodens, and complications it causes. Results: A total of 39 mesiodentes were found in 30 patients. the gender ratio was 2:1, but the difference was not statistically significant (p=0.2). Mesiodentes were most common in the conical form, followed by the tuberculate and the least supplemental. Seventy-seven percent of the mesiodentes are located vertically, 15% horizontally, and 8% inverted; 51% erupted, and 49% impacted. With a rate of 43%, displacement or axial rotation of the permanent central incisors was the most common complication. The delayed eruption was the second most common complication (%37). Diastema was noted in 27%. Cyst formation was noted in 7%. There was a statistically significant relationship between the number of mesiodentes seen simultaneously and the number of complications (p=0.022). Conclusion: The prevalence of mesiodens was determined to be 0.37% in the analyzed population, consistent with the literature. At least one mesiodens-related complication was noted in 80% of patients. As for complications, the number of concurrent mesiodentes observed is significant. Complications can be avoided by early diagnosis and timely surgical intervention.